2022
DOI: 10.3390/ma15155458
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study on the Rejuvenation Efficiency of Compound Rejuvenators for the Characterization of the Bituminous Binder, Mortar, and Mixture

Abstract: This study aims to comprehensively investigate the rejuvenation efficiency of various self-developed compound rejuvenators on the physical, mechanical, and aging properties of aged bitumen, asphalt mortar, and mixture. The results revealed that the restoration capacity of vacuum distilled-oil rejuvenators on high-and-low temperature performance-grade of aged bitumen is more significant. In contrast, an aromatic-oil based rejuvenator is good at enhancing low-temperature grade and aging resistance. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Figure 5 a shows that the penetration value increased linearly when the VCO content in the PAV-aged bitumen is augmented, as described by the linear fitting equation. A similar tendency was previously detected by Li et al [ 46 ]. Based on the rejuvenation purpose, the addition of VCO should be able to restore the penetration values of a PAV bitumen up to a RTFO aged state (30–45 dmm) (see the colored area in the Figure).…”
Section: Resultssupporting
confidence: 91%
“…Figure 5 a shows that the penetration value increased linearly when the VCO content in the PAV-aged bitumen is augmented, as described by the linear fitting equation. A similar tendency was previously detected by Li et al [ 46 ]. Based on the rejuvenation purpose, the addition of VCO should be able to restore the penetration values of a PAV bitumen up to a RTFO aged state (30–45 dmm) (see the colored area in the Figure).…”
Section: Resultssupporting
confidence: 91%
“…Many scholars have improved the road performance of asphalt mixtures through the improvement of asphalt materials [1]. Based on the influence of different rubber sizes on the waste rubber binder, Ren studied the continuous expansion degradation behavior and chemical rheological properties of crumb-rubber-modified asphalt [2]; Li discussed the influence of different regenerants on the performance of an asphalt mixture through selfdeveloped equipment and proposed the best maintenance conditions [3]. Their research provides a basis for the design of asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The third type examines how the fusion degree of recycled mixture affects its performance. Studies show that the density and Marshall stability of recycled asphalt mortar increase with an increase in curing temperature and time [36]. The research of Teng Wang and Jinzhi Xu et al [37,38] showed that as the placement time increases, the fusion degree of recycled mixture will continue to increase until complete fusion is achieved.…”
Section: Introductionmentioning
confidence: 99%